2019
DOI: 10.1101/741744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Angiosarcoma Project: enabling genomic and clinical discoveries in a rare cancer through patient-partnered research

Abstract: Despite collectively accounting for 25% of tumors in U.S. adults, rare cancers have significant unmet clinical needs as they are difficult to study due to low incidence and geographically dispersed patient populations. We sought to assess whether a patientpartnered research approach using online engagement can overcome these challenges and accelerate scientific discovery in rare cancers, focusing on angiosarcoma (AS), an exceedingly rare sarcoma with a dismal prognosis and an annual U.S. incidence of 300 cases… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(122 citation statements)
references
References 45 publications
6
114
2
Order By: Relevance
“…These POT1 mutations were distributed across all conserved domains. Our analyses of angiosarcoma tumour genomes revealed a high frequency of POT1 mutations distributed in a similar pattern, complementing other emerging studies that have observed a high frequency of POT1 mutations in angiosarcoma 33. Because the database lacks family history data, the cases profiled in the current study may contain patients meeting criteria for LFLS.…”
Section: Discussionsupporting
confidence: 81%
“…These POT1 mutations were distributed across all conserved domains. Our analyses of angiosarcoma tumour genomes revealed a high frequency of POT1 mutations distributed in a similar pattern, complementing other emerging studies that have observed a high frequency of POT1 mutations in angiosarcoma 33. Because the database lacks family history data, the cases profiled in the current study may contain patients meeting criteria for LFLS.…”
Section: Discussionsupporting
confidence: 81%
“…We noted that each canine cancer type shares major pathway alterations with its human counterpart ( Figure 2), including breast cancer, pediatric and adult glioma, diffuse large B-cell lymphoma, oral melanoma, osteosarcoma, or angiosarcoma 3,4,[24][25][26][27] . In both species, p53 pathway alteration and cell cycle alteration are common in osteosarcoma and oral melanoma ( Figures 2D and 2E).…”
Section: Each Cancer Type Has Distinct Molecular Featuresmentioning
confidence: 99%
“…Mutated genes and altered pathways in human cancers were extracted from published studies, including 996 breast cancers 24,25 , 91 high grade pediatric gliomas 40,41 , 507 adult low grade gliomas 12 , 48 diffuse large B-cell lymphomas 25 , 65 oral melanomas 27 , 58 pediatric osteosarcomas 3,4 , and 48 angiosarcomas 26 .…”
Section: Comparison Of Genomic Alterations Between Canine and Human Cmentioning
confidence: 99%
See 2 more Smart Citations